2012
DOI: 10.1074/jbc.m112.374041
|View full text |Cite
|
Sign up to set email alerts
|

Lipolytic Products Activate Peroxisome Proliferator-activated Receptor (PPAR) α and δ in Brown Adipocytes to Match Fatty Acid Oxidation with Supply

Abstract: Background: Adrenergic activation of brown adipocytes mobilizes fatty acids for oxidation and promotes transcription of oxidative genes. Results: Activation of adipocyte lipases generates agonists of PPAR␣ and PPAR␦ that promote transcription of oxidative genes. Conclusion: Lipolytic products signal via PPAR␣ and PPAR␦. Significance: Lipolytic activation of PPAR␣ and PPAR␦ provides a mechanism for matching oxidative capacity to substrate supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
167
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(175 citation statements)
references
References 54 publications
8
167
0
Order By: Relevance
“…Furthermore, the activation potential of PPAR␣ is enhanced by lipolytic products (30). We observed both increased lipolysis (Fig.…”
Section: Nat8l Is Expressed In Adipocytes and Located In Mitochondriamentioning
confidence: 48%
“…Furthermore, the activation potential of PPAR␣ is enhanced by lipolytic products (30). We observed both increased lipolysis (Fig.…”
Section: Nat8l Is Expressed In Adipocytes and Located In Mitochondriamentioning
confidence: 48%
“…Because cAMP signaling has been shown to activate PPARd, 45,46 it is possible that PPARd plays a role in the effect of iloprost on APP processing. Indeed, iloprost treatment increased PPARd protein expression (Figure 3(a)).…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated that PPARd-siRNA abolished iloprostinduced expression of ADAM10, indicating that PPARd was a major mediator of the iloprost-induced expression of ADAM10. Since cAMP signaling has been shown to activate PPARd, 8,45,46 it is likely that activation of IP-cAMP signaling augments ADAM10 expression via activation of PPARd (Figure 7). It has also been reported that in vitro both PGI 2 and iloprost could directly bind to PPARd, 8,58,59 therefore, we cannot rule out the possibility that direct activation of PPARd by iloprost might contribute to increase in expression of ADAM10.…”
mentioning
confidence: 99%
“…ATGL-mediated lipolysis is also required for functional PPAR-α and PPAR-δ signaling in oxidative tissues and the pancreatic β-cell, respectively (16,(33)(34)(35). For example, absence of ATGL in cardiac muscle leads to reduced PPARα-mediated mitochondrial biogenesis, substrate oxidation, and respiration, resulting in the lethal cardiomyopathy (16).…”
Section: Discussionmentioning
confidence: 99%